KETERAMPILAN HUBUNGAN SOSIAL SANTRI DI PESANTREN - Istihana, Istihana (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
Islamic Boarding school   is one of the non-formal education, to provide space for young muslims. Along with the demands higher especially in terms of social skill to walk life in world modern. Seems to have gained recognition as boarding powerful of citizens as the Islamic education institution that it is not only students to equip the religious side, but also, no less important is the legitimate skill for  social  life.  This  is  what  makes  boarding  there  is  now  no  longer  seen  as education deficit, which is identical to an educational institution and considered a second-class.It was indicated with the Islamic Boarding school  to the peculiarities of each, and excellence so the public school education of one who mimics the boarding or boarding which recognized by there is Islamic boarding school.